SEGMENTASI PASAR PENGGUNA JASA ANGKUTAN KERETA API PERKOTAAN TANAHABANG-SERPONG - Pradono Pradono; Miming Miharja; Awang Meindra (Jurnal Transportasi, 2011)
KRL transport operator should be able to create specific products in order to answer the demands and needs of service users. This study aims to determine market segmentation and positioning of the user of KRL Tanahabang-Serpong line based on class of service. Analyses were performed using the methods of K-Means Cluster and correspondence analysis. The results suggest that the market of KRL Tanahabang-Serpong line can be divided into 3 segments, namely segment of the upper class which is not too concerned with price, segment of the middle-class which is realistic on price, and segment of lower class which is oriented on price only. From the mapping results of the user's perception of the KRL services, it is found that there is an associative relationships of the product image in the minds of consumers, namely KRL Express - Fast and On Time, KRL Economy with AC - Comfortable and Affordable, and KRL Economy - Cheap.Keywords: KRL, market segmentation, perceptual maps, product image.